An APC Mutation in a Large Chinese Kindred With Familial Adenomatous Polyposis Was Identified Using Both Next Generation Sequencing and Simple STR Marker Haplotypes - Zhan, Qitao; Wang, Liya; Xu, Xiangrong; Sun, Yan; Li, Lejun; Qi, Xuchen; Chen, Feng; Wei, Xiaoming; Raff, Michael L.; Yu, Ping; Jin, Fan (Frontiers in Genetics, 2020)
Background Familial adenomatous polyposis (FAP) is an autosomal dominant disorder characterized primarily by the development of numerous adenomatous polyps in the colon and a high risk for colorectal cancer. FAP is caused by germline mutations of the adenomatous polyposis coli (APC) gene. The proband in this family was a 39-year-old female patient with the pathologic diagnosis of adenomatous polyps, and then a five-generation kindred with FAP was characterized in the following years. This article identified an APC mutation, and demonstrated the practical use of APC-linked STR markers, which could be used to reduce misdiagnosis of prenatal diagnosis or preimplantation genetic diagnosis resulted from contamination or allele drop-out. Methods Next-generation sequencing was used to identify the possible APC mutations in an affected individual from a family with autosomal dominant colon cancer. Targeted sequencing then used to identify additional related individuals with the mutation. Three short tandem repeat (STR) loci, D5S299, D5S134 and D5S346, were used for PCR-based microsatellite analysis of the APC gene in the extended family. Results We identified an APC: p.W553X mutation. The STR haplotype at the APC locus, A1B4C1, was shared by all clinically affected individuals with the APC: p.W553X mutation. In addition, the APC: p.D1822V variant was observed in 40% affected individuals and in two unaffected individuals. Conclusions We described a protein truncation mutation, APC: p.W553X; demonstrated the value of APC-linked STR markers (D5S299, D5S134 and D5S346) haplotypes; and suggested the potential role of these haplotypes in detecting loss of heterozygosity of the APC gene.